2021
DOI: 10.3390/ijms23010390
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Application of Regulatory T Cells in Diabetes Mellitus Type 1

Abstract: The autoimmune reaction against the beta cells of the pancreatic islets in type 1 diabetes mellitus (T1DM) patients is active in prediabetes and during the development of the clinical manifestation of T1DM, but it decreases within a few years of the clinical manifestation of this disease. A key role in the pathogenesis of T1DM is played by regulatory T cell (Treg) deficiency or dysfunction. Immune interventions, such as potential therapeutic applications or the induction of the Treg-cell population in T1DM, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…identified that in A53 transgenic (A53T) PD mice, the expression levels of cytotoxic-T-lymphocyte-antigen-4 (CTLA-4) and inducible costimulator (ICOS) were markedly reduced in T regulatory lymphocytes (Tregs), a critical player in maintaining immune homeostasis ( 63 ). Similarly, Tregs were also found to exhibit functional defects in PD patients, implying an abolished suppressive effect on autoimmune response and a contributory factor for the emergence of T1D ( 64 ). Meanwhile, in the reverse direction MR analysis, we failed to observe a causal effect of T1D on the susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…identified that in A53 transgenic (A53T) PD mice, the expression levels of cytotoxic-T-lymphocyte-antigen-4 (CTLA-4) and inducible costimulator (ICOS) were markedly reduced in T regulatory lymphocytes (Tregs), a critical player in maintaining immune homeostasis ( 63 ). Similarly, Tregs were also found to exhibit functional defects in PD patients, implying an abolished suppressive effect on autoimmune response and a contributory factor for the emergence of T1D ( 64 ). Meanwhile, in the reverse direction MR analysis, we failed to observe a causal effect of T1D on the susceptibility to PD.…”
Section: Discussionmentioning
confidence: 99%
“…While Tregs can have a suppressive effect on autoreactive T cells and prevent the development of autoimmune diseases, they may also exhibit functional defects in AD patients ( 53 ). These defects might limit their ability to effectively control immune responses, ultimately leading to the activation of autoreactive T cells that target pancreatic beta cells and contribute to the development of T1D ( 54 , 55 ). In addition, heightened production of pro-inflammatory cytokines generated by Th17 cells has demonstrated a positive correlation with the emergence of type 1 diabetes (T1D) ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials using Treg have shown improved but not as promising results as expected, with only a few clinical studies showing that higher levels of Tregs and IL2 appear to improve endogenous insulin secretion in T1D, and the exploration of insulinogenic-specific Tregs in the immune response of patients with T1DM needs to continue in-depth ( 34 37 ). Therefore, how to use Tregs to target the autoimmunity against islet β cells that occurs in T1D has become a hot topic in scientific research ( 38 , 39 ). In many studies using a mouse model of autoimmune diabetes, the use of IL-2 to modulate Treg was found to reduce interferon production by pancreatic infiltrating T cells, increase beta-cell numbers, and mitigate other immune therapies that interfere with Treg homeostasis and prevent disease ( 40 42 ).…”
Section: Tregs Cells In T1dmentioning
confidence: 99%